The effects of cultural distance on multi-unit firms - Benedikt Rydzek; Peter Egger; Raymond Riezman (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper we develop a model to analyze the effects of (country-pair-specific) costs of creating, transferring and accessing intangible assets for multi-unit firms. These costs might vary with the cultural distance between countries, such as the difference in language, work ethics or other moral values. We argue that these costs are an important factor to explain why most firms are single unit firms, most multi-unit firms have only one affiliated unit and why multinational firms are only a tiny fraction of all firms in a country. Therefore, we develop a model with heterogeneous firms that produce differentiated goods in different firm units. The number of units depends on the costs of transferring intangible assets. If these costs are relatively high, most firms will be single unit firms. Furthermore, if costs of transferring intangible assets to an affiliated firm in a foreign country are even higher, only the most productive firms will be multinational firms. Additionally, multinational firms will be open more affiliated firms in countries that are culturally closer to their home country. These findings square with stylized facts and estimation results presented in the paper.
Keywords: F23; L11; L25; 330